Localized Pigmented Villonodular Synovitis of the Posterior Knee Compartment with Popliteal Vessel Compression: A Case Report of Arthroscopic Resection Using Only Anterior Knee Portals - Jack Daoud; Dany Aouad; Youssef Hassan; Georges El Rassi (Case Reports in Orthopedics)
Background. Pigmented villonodular synovitis is a rare pathology causing hyperplasia of the synovium. It mostly affects young populations and most commonly the knee joint. It rarely affects the posterior compartment of the knee as the case presented in this study. Open surgery is usually used to treat this condition; however, in our case it was excised arthroscopically despite the anatomical challenges of the posterior knee compartment. Case Presentation. This case presents a female patient with a complaint of posterior-region pain of her left knee post direct trauma post fall. This was directly followed by knee joint blockage for 1-week duration before presentation to the hospital. On MRI, she was found to have a multiloculated hemosiderin-containing structure of synovial origin within the femoral notch, extending beyond the joint capsule displacing the popliteal vessels. The patient underwent arthroscopic resection of the lesion, which was found to be pigmented villonodular synovitis on anatomopathological examination. On 6-month follow-up, the patient showed good clinical evolution with the absence of symptoms and back-to-normal daily activities. Conclusion. This is a rare case of PVNS affecting the posterior knee joint compartment of a middle-aged woman, which was successfully excised arthroscopically, with no residual affected tissue or recurrence on 6-month follow-up.